Building high-performance integrated optical devices using subwavelength grating metamaterials - Sánchez-Postigo, Alejandro; Ginel-Moreno, Pablo; Ortega-Moñux, Alejandro; Wanguemert-Pérez, Juan Gonzalo; Halir, Robert; Pereira-Martín, Daniel; Hadij-El-Houati, Abdelfettah; Schmid, Jens H.; Wang, Shurui; Vachon, Martin; Xu, Dan-Xia; Ye, Winnie N.; et al. (My University, 2021)
The use of subwavelength grating structures in silicon waveguides have fuelled the development of integrated optical components with superior performance. By a judicious lithographic pattern of the grating, the optical properties of the synthesized metamaterial can be accurately tailored. In this work, we review our latest advances in subwavelength-grating-engineered silicon and germanium planar devices.
Ministerio de Ciencia, Innovación y Universidades (MCIU) (PID2019-106747RB-I00), Consejería de Economía, Conocimiento, Empresas y Universidad (CECEU) (UMA18-FEDERJA-219, P18-RT-1453, P18-RT-793) and National Research Council of Canada (NRC) Collaborative Science, Technology and Innovation Program (CSTIP) (HTSN 209).
Keywords: Fibras ópticas; Silicio